The influence of workload, salary and coworker towards job satisfaction among employees - Mohamad Faridthul Azhar, Mohd Noor (2018)
Job Satisfaction is an important aspect for every organization so the main aim of this study is to examine the influence of workload, salary and coworker on job satisfaction toward employees. The objective of this study is to examine the influence of every independent variable on job satisfaction. The study involved 123 numbers of employees. This is a quantitative research so in order to analyze the data that been collected Statistical Package for Social Science (SPSS) has to be used in order to see the relationship between independent variables which is workload, salary and coworker on dependent variable which is job satisfaction. This study had recognized workload, salary and coworker as a factor that may influence job satisfaction. According to the multiple regression analysis every independent variables got positive relationship with dependent variables but what make it differences was workload do not have significant positive relationship with job satisfaction compare to salary and coworker. More importantly, based to findings salary and coworker will positively influence job satisfaction but for the workload case this variables will not positively influence job satisfaction. Finally from the researcher point of view the organization should play a significant role in order to keep their employee satisfy because it may bring so many benefits to the organization and researcher also will provides a recommendation to the organization in this study.